Deciphering role of FGFR signalling pathway in pancreatic cancer. (3rd April 2019) - Kang, Xiaodiao; Lin, Zeng; Xu, Minhui; Pan, Jun; Wang, Zhi‐wei
Abstract: Recently, fibroblast growth factors are identified to play a vital role in the development and progression of human pancreatic cancer. FGF pathway is critical involved in numerous cellular processes through regulation of its downstream targets, including proliferation, apoptosis, migration, invasion, angiogenesis and metastasis. In this review article, we describe recent advances of FGFR signalling pathway in pancreatic carcinogenesis and progression. Moreover, we highlight the available chemical inhibitors of FGFR pathway for potential treatment of pancreatic cancer. Furthermore, we discuss whether targeting FGFR pathway is a novel therapeutic strategy for pancreatic cancer clinical management.